Importance of the historical context in philosophy: the case of the moral philosophy of David Hume (ALPHA. Journal of Arts, Literature and Philosophy, 2018)
This article raises the need of a historical approach to philosophical texts taking as an example the case of David Hume’s ethics proposal. It shows Hume`s interest in participating actively in the intellectual dialogue of his time and his intention to integrate the scientific method into the moral sciences and how his critique of reason must be understood in this light. To do this, we quickly mention the intellectual atmosphere of the time and the positions in conflict in the philosophical debate of the 18th Century: relativistic skepticism, radical rationalism and naive sentimentality, noting that, deep down, Hume cannot be excluded completely from any of these positions but not typecast in any of them.
Keywords: David Hume; moral; history; hermeutics